ASPECTS RELATED TO THE PROPULSION HYDRAFOIL SHIPS - Levent ALI; Beazit ALI; Adrian POPA; Gheorghe SAMOILESCU (Fiabilitate şi Durabilitate)
In this paper, we analyze some aspects related to the propulsion of hydrofoil ships. They are very important for the success of the mission if they are military ships and for cargo security, if they are civilian transport ships, especially when navigating at high speed on their hydrofoil wings in rough sea conditions. This paper presents an original procedure for estimating the propulsion of hydrofoil ships. This procedure has enabled the development of a computer program that can predict both those types of ship propulsion regime imposed at a quasi-stationary speed and the march regime on wings. The calculation software obtained may serve to design any type of hydrofoil ship.